Resistive pulse sensing as particle counting and sizing method in microfluidic systems: Designs and applications review - Vaclavek, Tomas; Prikryl, Jan; Foret, Frantisek (Journal of separation science, 2019)
Resistive pulse sensing is a well-known and established method for counting and sizing particles in ionic solutions. Throughout its development the technique has been expanded from detection of biological cells to counting nanoparticles and viruses, and even registering individual molecules, e.g., nucleotides in nucleic acids. This technique combined with microfluidic or nanofluidic systems shows great potential for various bioanalytical applications, which were hardly possible before microfabrication gained the present broad adoption. In this review, we provide a comprehensive overview of microfluidic designs along with electrode arrangements with emphasis on applications focusing on bioanalysis and analysis of single cells that were reported within the past five years.
Keywords: Particle Size; analýza jednotlivých buněk; Single-Cell Analysis; Equipment Design; Electrodes; elektrody; Microfluidic Analytical Techniques; Humans; lidé; velikost částic; design vybavení; mikrofluidní analytické techniky